Benin Economic Update, Fall 2014 - World Bank (2014)
Benin has made substantial progress over the past decade in reinforcing macroeconomic stability, which has laid the foundation for modest but accelerating growth. After averaging less than 3.7 percent from 2007-2011, GDP growth rose to 5.4 percent in 2012 and reached 5.6 percent in 2013. Growth is expected to remain strong at 5.5 percent in 2014. Benin s enhanced growth performance has been supported by ongoing efficiency improvements at the Port of Cotonou, a vital regional trade hub, which have boosted traffic and cut marginal shipping costs. These developments have been complemented by stronger cotton and non-cotton agricultural production, which have been bolstered by favorable weather conditions and relatively effective management of recent cotton campaigns. The weak connectivity between macroeconomic growth and poverty reduction arises largely from the very modest growth of per capita income. In addition, the highly informal nature of the economy, low and declining productivity, particularly in agriculture, and a lack of economic diversification all contribute to the persistence of poverty in Benin. Agricultural growth has been driven by the expansion of cultivated land rather than by increased productivity. Similarly, the increasing size of the national labor force has made a far larger contribution to GDP than have increases in labor productivity. Growth in the formal, salaried labor market remains constrained, and few high productivity/high wage jobs are being created. Strengthening the links between growth and poverty reduction will require boosting productivity, enhancing the business and investment climate, and promoting formalization. In this context, the Benin Economic Update is designed to provide timely analysis of recent developments and contribute to the ongoing dialogue on sound macroeconomic management and effective poverty reduction.